Pemanfaatan Dokumenter Interaktif Dalam Teknologi Pembelajaran - Hesti Kusumaningrum (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2022)
Learning becomes challenging due to the insufficient knowledge transmission between teachers and pupils. Limitations, particularly in terms of the capacity to thoroughly explain science in relation to historical events, phenomena that may be utilized as lessons, and phenomena that can broaden students' understanding of science. Additionally, in order to carry out the teaching and learning process, instructors and students sometimes confront constraints on time and location. This essay makes an effort to explain interactive documentaries from the standpoint of new media as a phenomena of expanding educational demands. The research methodology utilized is a descriptive qualitative method, which uses qualitative data and is described descriptively. In line with the study's findings, learning challenges can be overcome by showing engaging and interactive documentaries tailored to the requirements of the students. This article demonstrates how the present innovation in documentary production is highly influenced by the growth of multimedia and internet technology.